The role of the Central Bank of Iraq in supporting private projects - Assistant Teacher Husam Ali Kadhem (مجلة الدراسات الاقتصادية والادارية)
The private sector constitutes a crucial pillar in driving economic growth and propelling the economy forward in various countries. Despite facing numerous setbacks in Iraq, starting from the adoption of socialist policies to the events of 2003 and the subsequent destruction of much of the infrastructure, the private sector has persevered. The Central Bank, recognizing its importance, has endeavored to revitalize this sector by providing the necessary capital for investment. The research reveals that the Central Bank's initiatives have contributed to financing approximately 8,294 projects, amounting to 322 billion dinars, and employing around 82,169 workers. However, the study suggests that financing alone is not the underlying cause of the private sector's growth or hindrance. The percentage of borrowing to the initiative's size indicates that while the private sector may suffer from insufficient funding, a 32% ratio (2016-2020) suggests that private investment is not solely tied to financing. The research recommends the necessity of establishing a partnership between the public and private sectors to achieve synergy, benefiting both sectors and fostering dynamic growth in the private sector. This collaboration is seen as instrumental in expanding private sector activities, enhancing its position, and simplifying procedures for investment licenses, including land allocation, tax incentives, and customs protection for its goods.